Francis Stephen of Lorraine: constructing a unique identity as male consort and prospective emperor, 1736–45 - Vagner-Clévenot, N (2024)
This thesis investigates the structural constraints of an eighteenth-century prince’s agency to shape his identity, through the case study of Francis Stephen of Lorraine. It studies Francis’s ‘exercise of princehood’, a notion coined in this research project that comprises his behaviour at court, his interactions with important individuals composing the latter and with wider socio-political elites, and his overseeing of the spread of his image to various audiences. These audiences are studied using an innovative methodology that structures them in concentric circles around the princely figure. The thesis shows that, between 1736 and 1740, as the husband of Maria Theresa, heiress of the Habsburg monarchy, Francis was usually unable to escape the structural constraints on his self-fashioning, but successfully acquired social capital. However, following Maria Theresa’s accession as queen in 1740, he was particularly useful in asserting his wife’s legitimacy on the throne by being an active performer of ceremonial continuity with her predecessors. Furthermore, he contributed to shape a new precedent as a male consort and an alternative figure of authority that was communicated to various types of audience—but did not always possess ultimate agency in these changes, unlike his wife. In addition, the thesis demonstrates that Francis mostly spread his identity to the Habsburg monarchy, thereby contributing to the creation of a distinct Habsburg dynastic identity, separate from the Holy Roman Empire. His case study also highlights the continued relevance of ceremonial issues not only for court culture, but also state-building and diplomacy in mid-eighteenth-century Europe. Finally, the rule of a married woman compelled contemporaries to conceptualise the role of the consort as separate from that of ruler of the monarchy. This in turn facilitated the embodiment of the growing notion of the state in the person of the sovereign.